Recent Publications (Quarterly Journal of Economics, 1957)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 71, Issue 1, February 1957, Pages 165–169, https://doi.org/10.1093/qje/71.1.165 Published: 01 February 1957